Nutrition Claims on Fruit Drinks Are Inconsistent Indicators of Nutritional Profile: A Content Analysis of Fruit Drinks Purchased by Households With Young Children - Duffy, Emily W. (J Acad Nutr Diet, 2020)
BACKGROUND: Fruit drinks are the most commonly consumed sugar-sweetened beverage among young children. Fruit drinks carry many nutrition-related claims on the front of package (FOP). Nutrition-related claims affect individuals’ perceptions of the healthfulness of products and purchase intentions, often creating a “health halo” effect. OBJECTIVE: The aims of this study were to describe the prevalence of FOP nutrition-related claims on fruit drinks purchased by households with young children and to examine the association between claims and the nutritional profile of fruit drinks. DESIGN: The sample included 2059 fruit drinks purchased by households with children 0 to 5 years old participating in Nielsen Homescan in 2017. FOP labels were obtained from 2 databases that contain bar code–level information on all printed material on product labels. A codebook was used to code for presence of FOP nutrition-related claims. The coded claims data were linked by bar code with Nutrition Facts label data. Claim type prevalence was calculated, and the association between claim types and median calories and total grams of sugar per 100 mL was analyzed using Wilcoxon rank-sum tests. The percentages of products containing noncaloric sweeteners (NCSs) with and without each claim type were also calculated and compared. RESULTS: Almost all (97%) fruit drinks sampled had at least 1 nutrition-related FOP claim. Implied natural claims such as “natural flavors” were the most common (55% of products), followed by claims about the presence of juice or nectar (49%). Claims about vitamin C (33%), sugar (29%), and calories (23%) were also common. Fruit drinks with vitamin C, juice or nectar, fruit or fruit flavor, and overt natural claims were higher in calories and sugar and less likely to contain NCSs compared with products without these claims. Fruit drinks with calorie, sugar, NCS, implied natural, and other claims were lower in calories and sugar and more likely to contain NCSs compared with products without these claims. CONCLUSIONS: Claims are prevalent on fruit drinks purchased by households with young children. This is concerning given prior research demonstrating that claims can mislead consumers. Regulatory actions such as requiring a warning or disclosure on drinks that contain added sugars or NCSs should be considered.